Evaluasi Iklim Kerja di Bagian Produksi pada Industri Keramik di Wilayah Gresik - Merry Sunaryo; Moch. Sahri (Puslitbang Sinergis Asa Professional, 2019)
Hot work climate starts from the emergence of heat energy that comes from a heat source that is emitted directly or through an intermediary and enters the work environment, and becomes a heat pressure as an additional burden on the workforce. This can worsen health conditions and labor stamina when added to the heavy physical workload. The ceramics industry requires special and unique techniques such as combustion. The hot work climate itself can affect the physical and mental condition of workers. The impact that often occurs in workers due to the heat of work is fatigue and dehydration. The purpose of this study is to analyze the conditions of the work climate in the work environment and evaluate the work climate in the production section, which will be compared to the threshold value so that it can be used as a basis for carrying out control measures in an effort to prevent occupational diseases in the industry. This research is a descriptive study, using a cross sectional study design. Measurements of work climate carried out on 4 companies in the ceramics industry in the Gresik region with 10 measurement points in each company, are known to have results, most of which have ISBB values> 30ºC. Observations that have been carried out workloads on the ceramics industry are moderate workloads with a working time of 75% -100% with 25% rest time. based on the results of an average of 10 points from the four companies the ISBB value of measurement results is greater than the value of the NAB that has been set, with a value of 28ºC NAB. Therefore, the need to control the work climate both in its environment and its workers. These controls are general controls such as training (education / training), heat pressure control through the application of hygiene.